Scaling in the Digital Initiative (Dx) - Woltering, Lennart; Valencia, Eva (International Maize and Wheat Improvement Center, 2023)
The Digital Initiative has a list of innovations that have been developed with the goal of accelerating the transformation towards sustainable and inclusive agrifood systems by generating researchbased evidence and innovative digital solutions. From these innovations, four were selected to assess their scaling potential and develop potential scaling strategies so they increased their impact. Two of these innovations decided to use the digital tool of the Scaling Scan to assess their scalability potential. The results of these assessments showed that the main enabling condition for them to scale is to develop credible evidence of their digital solution. In particular, the main action to scale the innovation should be focused on finding finance and public sector governance support. In comparison, the audio-processing innovation requires greater application of this innovation in case studies so that there is credible evidence that may promote other users (other agri-food NGOs) to scale this innovation in their own work. Moreover, both these innovations show strong leadership and management as a strength to continue the scaling of these innovations in different contexts. However, more application of these innovations is required for these innovations to increase their feedback and credibility to be applied in different contexts. This shows that the work in generating innovative digital solutions is positive, but there is a window of opportunity to create evidence on using these innovations and to generate research-based evidence.